Melatonin ameliorates oxidative organ damage induced by acute intra-abdominal compartment syndrome in rats - (:unkn) unknown (WILEY, 2003)
Acutely increased intra-abdominal pressure (IAP) can lead to multiple organ failure. As blood flow to intra-abdominal organs is reduced by high venous resistance, ischemia-reperfusion (I/R) injury plays an important role in the pathogenesis of abdominal compartment syndrome (ACS) following IAP. Melatonin, a secretory product of the pineal gland, is known to have free radical scavenging and antioxidative properties in several oxidative processes. The objective of this study was to examine the potential protective properties of melatonin on the oxidative organ damage in a rat model of ACS. Under ketamine anesthesia, an arterial catheter was inserted intraperioneally (i.p.) and using an aneroid manometer connected to the catheter, IAP was kept at 20 mmHg ( ischemia group; I) for 1 hr. In the ischemia/reperfusion (I/R) group, pressure applied for an hour was decompressed and a 1-hr reperfusion period was allowed. In another IR group, melatonin was administered ( 10 mg/kg, i.p.) immediately before the decompression of IAP. The results demonstrate that tissue levels of malondialdehyde (MDA) and myeloperoxidase activity (MPO; index of tissue neutrophil infiltration) were elevated, while glutathione (GSH; a key to antioxidant) levels were reduced in both I and I/R groups ( P < 0.05 - 0.001). Melatonin treatment in I/R rats reversed these changes ( P < 0.01 - 0.001). Moreover, melatonin given to the I/R group reduced the elevations in serum aspartate aminotransferase, alanine aminotransferase and blood urea nitrogen levels and abolished the increase in serum creatinine levels. Our results indicate that melatonin, because of antioxidant and free radical scavenging properties, ameliorates reperfusion-induced oxidative organ damage. In conclusion, the results of the present study suggest that the therapeutic value of melatonin as a 'reperfusion injury-limiting' agent must be considered in ACS.
Keywords: abdominal compartment; antioxidant; glutathione; lipid peroxidation; melatonin; myeloperoxidase; INTRA-ABDOMINAL PRESSURE; ISCHEMIA-REPERFUSION; MYELOPEROXIDASE ACTIVITY; BACTERIAL TRANSLOCATION; LIPID-PEROXIDATION; TISSUE-INJURY; FREE-RADICALS; GLUTATHIONE; PROTECTION; LIVER